Lineages and trajectories: Vol 1 - Lineages - Abbasy-Asbagh, Ghazal; Acosta, Marcela; Johanesen, Karilyn; Rew, Margaret (New York Actar, 2014)
At a time when fundamentals of design education are being questioned and studios are being used as laboratories for everything ranging from design-build and fabrication practices to community service, material research, and multidisciplinary incubators, this volume of Catalyst positions the current pedagogy at the University of Virginia School of Architecture within an extended history of the school through an archival project that traces the lineages of its faculty. It considers design pedagogy through the lens of the formative experiences and agendas of the faculties of the Departments of Architecture and Landscape Architecture, examining their role in shaping the school$1 (Bs direction, independent of top-down mandates and institutional agendas. s With contributions of Ghazal Abbasy-Asbagh, Marcela Gracia Acosta, Karilyn Johanesen, Margaret Rew, Sam Eldredge, Del Hepler, Bess Lovern, Kaitlynn Long, Seth Salcedo, Emily Richards and University of Virginia School of Architecture Faculty, Students, and Alumni
Keywords: ARCHITECTURE EDUCATION (AR-EDU)